Waste-Derived Cellulosic Fibers and Their Applications - Antony V. Samrot; Khosa Tariro Ngaakudzwe; D. Rajalakshmi; P. Prakash; S. Suresh Kumar; M. Chandramohan; D. Alex Anand; J. Lilly Mercy; Yishak Simon; S. Saigeetha (Advances in Materials Science and Engineering)
The use of bio-based materials has become a focus of research nowadays. For the development of new generations of advanced resources, renewable and available resources must be combined with advanced technologies. Researchers have looked into biomass and waste cellulosic materials as sustainable sources for nano-crystalline cellulose extraction. Besides the different treatment methods suitable for various applications, this review aims to provide integrated details on the extraction methods and applications of cellulosic fibers and cellulose nanocrystals derived from wastes of different sources. There are numerous applications including building materials, electronics, furniture, automobiles, medical applications, sports goods, filtrations, water purification, and delivery systems of drugs which have been discussed.